The Role of Resources in Strategic Management of Enterprise Роль ресурсов в стратегическом управлении предприятиями - Predein Andrey M. (Bìznes Inform, 2012)
The article considers the notion of "resources of the enterprise" as well as the evolution of ideas in the resource-based approach. It also presents its own definition of "strategic resources of the enterprise" and its classification. Developed a simulation model for management of strategic resources. В статье рассмотрено понятие «ресурсы предприятия», а также эволюция идей ресурсного подхода в процессе управления предприятием. Также представлено собственное определение понятия «стратегические ресурсы предприятия» и их классификация. Разработана имитационная модель управления стратегическими ресурсами.